Long term antithrombotic treatment in atrial fibrillation patients undergoing coronary surgery. (25th November 2020) - Skibniewski, M; Venetsanos, D; Janzon, M; Karlsson, L; Lawesson Sederholm, S; Nielsen, S.J; Jeppsson, A; Alfredsson, J
Abstract: Introduction: Current revascularisation guidelines from ESC recommend treatment with oral anticoagulants (OAC) alone in atrial fibrillation (AF) patients treated with coronary artery by-pass grafting (CABG), after one year of treatment with OAC and platelet inhibition (PI). Little is known about current treatment practice and there is a paucity of evidence to guide decision making. Purpose: To assess treatment patterns and clinical outcome of OAC as sole antithrombotic treatment one year after CABG in patients with a history of AF, in comparison to PI only and OAC+PI. Method: We included 2 112 patients (out of 32908 who underwent isolated CABG) from 2006 to 2014 with a history of atrial fibrillation, alive one year after surgery and a CHA2DS2-VASC-score ≥2. Based on data on individual dispensed prescriptions 1 to 1.5 years after surgery, patients were assigned to one of three treatment arms: PI alone (n=931), OAC alone (n=814) or combination of OAC+PI (n=367). Differences in MACE (death, myocardial infarction [MI] and stroke) between the three groups were assessed using a Cox regression model. Data are presented as hazard ratios (HR) with 95% confidence intervals [CI], adjusted for CHA2DS2-VASC-score (which include age, sex, hypertension [HT], congestive heart failure [CHF], stroke, vascular disease and diabetes) for MACE and the individual components of MACE; and CHA2DS2-VASC+history of bleeding regarding readmission for bleeding. Median follow-up was 3 years, range (0.5–3). Results: Patients treated with PI only were younger (71, 72 and 73 years) and less often had HT (62%, 72 and 70%), and CHF (30, 40 and 40%) in the PI, PI+OAC and OAC groups respectively. Patients treated with PI only, more often had a history of MI (54%) compared to OAC (42%) but not to PI+OAC (53%). The cumulative incidence of MACE at three years was 18.9, 14.0 and 14.9% in the PI, PI+OAC and OAC groups, respectively. The corresponding numbers were for death 9.9, 9.0 and 11.2%, MI 4.6, 3.5 and 1.9%, stroke 6.0, 2.7 and 2.7% and readmission for bleeding 5.9, 11.3 and 7.0%, respectively. After adjustment, PI only was associated with significantly higher risk for MACE (HR 1.36, 95% CI: 1.06–1.75), MI (HR 2.82, 95% CI: 1.47–5.40), and stroke (HR 2.34, 95% CI: 1.36–4.02); while PI+OAC was associated with higher risk for MI (HR 2.43, 95% CI: 1.09–5.34) and bleeding complications (HR 1.58, 95% CI: 1.01–2.46), compared to OAC only. Conclusions: In CABG patients with a history of AF and an indication for OAC, one year after surgery, treatment with OAC alone was associated with lower MACE rate than PI alone, driven by lower rates of MI and stroke. In addition, OAC only was associated with less bleeding complications than PI+OAC. These real-world data provide support to current ESC guidelines recommending OAC alone one year after CABG surgery. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): County council of Östergötland, Sweden